Macronutrient and micronutrient intake in dietary habits contributed to dyspeptic symptoms in Indonesia - Miftahussurur, Muhammad; Alfaray, Ricky Indra; Ayu Rezkitha, Yudith Annisa; Afrida Fauzia, Kartika; Maulahela, Hasan; Muzellina, Virly Nanda; Mariana Rotty, Luciana Sophie; Namara, Yoma Sari; Abubakar, Azzaki; Mustika, Syifa; Ratnasari, Neneng; Santosa, Agus Yudho; et al. (Gaceta Médica de Caracas, 2022)
Background: Dyspepsia is a highly prevalent gastrointestinal disorder and assessing the nutrient correlation is important to improve the patient’s dyspepsia. We analyzed the association of the macronutrients and micronutrients with dyspepsia also its correlation to the severity of dyspepsia.